1994
DOI: 10.2337/diacare.17.10.1110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recurrent Practice at Home on the Acceptability of Capillary Blood Glucose Readings: Accuracy of self blood glucose testing

Abstract: Clinically acceptable user proficiency in capillary blood glucose testing can be maintained in most subjects, with recurrent intensive education during follow-up clinic visits. Therefore, we recommend that these comparisons be performed and patient's technique be observed at each visit to monitor their performance. The clinic glucose meter is a suitable alternative to a clinical laboratory for user proficiency checks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Only 45% of the patients' measurements were within 10% of the hexokinase value, and only 63% were within 15%; these figures fall far short of the ADA benchmarks. In addition, these results are in accord with numerous studies that report the failure of patients to achieve the ADA goal for SMBG accuracy (14)(15)(16)(17) The new EG was created to reflect the opinion of a large number of clinical diabetes experts. The consensus EG lacks the discontinuities of Clarke et al' s EG but, otherwise, it gives similar results.…”
Section: Figure 1-egs For Type 1 Diabetes (A) and Type 2 Diabetes (B)supporting
confidence: 66%
“…Only 45% of the patients' measurements were within 10% of the hexokinase value, and only 63% were within 15%; these figures fall far short of the ADA benchmarks. In addition, these results are in accord with numerous studies that report the failure of patients to achieve the ADA goal for SMBG accuracy (14)(15)(16)(17) The new EG was created to reflect the opinion of a large number of clinical diabetes experts. The consensus EG lacks the discontinuities of Clarke et al' s EG but, otherwise, it gives similar results.…”
Section: Figure 1-egs For Type 1 Diabetes (A) and Type 2 Diabetes (B)supporting
confidence: 66%
“…Patient factors are also important, particularly adequate training. Recurrent education at clinic visits and comparison of SMBG with concurrent laboratory glucose analysis improved the accuracy of patients' blood glucose readings (118 ). Thus, it is important to evaluate the patient's technique at regular intervals (21 ).…”
Section: Rationalementioning
confidence: 99%
“…However, this list (5,7-11) is incomplete, with there being many additional studies incorporating EGA (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). What is important to point out is that in all of these published studies the authors reported both EGA results and standard statistical results.…”
mentioning
confidence: 99%